36-month clinical outcomes of patients with venous thromboembolism: GARFIELD-VTE. Issue 222 (February 2023) - Turpie, Alexander G.G.; Farjat, Alfredo E.; Haas, Sylvia; Ageno, Walter; Weitz, Jeffrey I.; Goldhaber, Samuel Z.; Goto, Shinya; Angchaisuksiri, Pantep; Kayani, Gloria; Lopes, Renato D.; Chiang, Chern-En; Gibbs, Harry; et al.
Abstract: Background: Venous thromboembolism (VTE), encompassing both deep vein thrombosis (DVT) and pulmonary embolism (PE), is a leading cause of morbidity and mortality worldwide. Methods: GARFIELD-VTE is a prospective, non-interventional observational study of real-world treatment practices. We aimed to capture the 36-month clinical outcomes of 10, 679 patients with objectively confirmed VTE enrolled between May 2014 and January 2017 from 415 sites in 28 countries. Findings: A total of 6582 (61.6 %) patients had DVT alone, 4097 (38.4 %) had PE ± DVT. At baseline, 98.1 % of patients received anticoagulation (AC) with or without other modalities of therapy. The proportion of patients on AC therapy decreased over time: 87.6 % at 3 months, 73.0 % at 6 months, 54.2 % at 12 months and 42.0 % at 36 months. At 12-months follow-up, the incidences (95 % confidence interval [CI]) of all-cause mortality, recurrent VTE and major bleeding were 6.5 (7.0–8.1), 5.4 (4.9–5.9) and 2.7 (2.4–3.0) per 100 person-years, respectively. At 36-months, these decreased to 4.4 (4.2–4.7), 3.5 (3.2–2.7) and 1.4 (1.3–1.6) per 100 person-years, respectively. Over 36-months, the rate of all-cause mortality and major bleeds were highest in patients treated with parenteral therapy (PAR) versus oral anti-coagulants (OAC) and no OAC, and the rate of recurrent VTE was highest in patients on no OAC versus those on PAR and OAC. The most frequent cause of death after 36-month follow-up was cancer (n = 565, 48.6 %), followed by cardiac (n = 94, 8.1 %), and VTE (n = 38, 3.2 %). Most recurrent VTE events were DVT alone (n = 564, 63.3 %), with the remainder PE, (n = 236, 27.3 %), or PE in combination with DVT (n = 63, 7.3 %). Interpretation: GARFIELD-VTE provides a global perspective of anticoagulation patterns and highlights the accumulation of events within the first 12 months after diagnosis. These findings may help identify treatment gaps for subsequent interventions to improve patient outcomes in this patient population.